Service Quality of Google Pay - binti Abdul Rashid, Asma Fadzlin; binti Mohd Shafiee, Auni Shahirah; Bin Hazren, Arsyad Syafie; Mansoor, Atfaan; Yusof, Dr. Rosmelisa; Hui, Dr. Gan Kia; Putra, Alvin Nugraha; Rachmanu, Alya Aprilya; Jain, Puneet (Asia Pacific Journal of Management and Education (APJME), 2023)
This study aims to evaluate service quality while using Google Pay. This study demonstrates that digital payment is emerging as an important platform in realizing the Go Cashless mission. Due to world globalization, this industry has become more significant since people nowadays are more comfortable with making an online transaction. Hence, it is more justifiable to take further action in making digital payments a norm. This research project aims to understand the factors that influence service quality of Google Pay. Many factors can influence the satisfaction of the users. However, this study will focus on perceived risk, perceived usefulness, perceived ease of use and awareness. For the research methodology, we collect data from users using a questionnaire and analyze the result using SPSS. This study is believed to help us in understanding the major factors that can impact Google Pay’s service quality.